Functional analysis of T lymphocyte subsets in antiviral host defense. - Leist, T; Cobbold, S; Waldmann, H; Aguet, M; Zinkernagel, R (1987)
The role of different T cell subsets in antiviral host defense was investigated by treating thymectomized C57BL/6 and CBA/J mice with monoclonal rat anti-Lyt-2 or anti-L3/T4 IgG 2b antibodies 14 and 10 days before infection. This treatment depleted the respective T cell subsets to undetectable levels in peripheral blood when assayed by immunofluorescence. In mice treated with anti-Lyt-2, induction of cytotoxic T cells was reduced to less than 1 to 2% after intravenous infection with Armstrong strain of lymphocytic choriomeningitis virus (LCMV). In addition, no primary swelling of the footpad could be detected following local inoculation of the virus. In animals treated with anti-L3/T4, antiviral cytotoxic T lymphocyte responses were reduced by a factor of 10. These L3/T4+ cell-depleted mice showed delayed footpad swelling after local injection of LCMV Armstrong. After intracerebral infection with LCMV, anti-Lyt-2-treated mice were resistant and those injected with anti-L3/T4 were totally susceptible to LCMV Armstrong-triggered immunopathologic disease. Virus could be detected in the blood of antibody-treated mice 7 days after inoculation; however, no virus could be measured in the blood of surviving anti-Lyt-2-treated animals 15 days after intracerebral infection. Serum titers of interferon-alpha,beta induced by viral infection remained unaffected by depletion of T cell subsets. Anti-L3/T4 antibody-treated C57BL/6 mice failed to generate IgG antibodies against the New Jersey strain of vesicular stomatitis virus, whereas Lyt-2+ cell-depleted mice had normal antivesicular stomatitis virus (New Jersey strain) IgG antibody titers.